1997
DOI: 10.1095/biolreprod57.6.1285
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of Human Placental Corticotropin-Releasing Factor by Prostaglandins and Estradiol1

Abstract: The mechanism of labor initiation in humans has not been completely elucidated. Prostaglandins, estrogens, and corticotropin-releasing factor (CRF) have all been shown to affect uterine myocytes and enhance uterine contractility. There are also indications that these uterine regulators have additional effects on other sites involved in labor and that they may act in concert or, perhaps, by regulating each other. Therefore, we evaluated the CRF promoter for transcriptional regulation by prostaglandins and estro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…In the placenta and fetal membranes, the production of PGE 2 and PGF 2a was enhanced by CRH in vitro (Jones and Challis, 1989). Since PGE 2 (Dibbs et al, 1997) and interleukin 1b (Petraglia et al, 1990) themselves increase the CRH synthesis of trophoblast cells, this may constitute a positive paracrine feedback loop resulting in labour and delivery. In addition, CRH stimulates the synthesis of oxytocin in the placenta (Florio et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In the placenta and fetal membranes, the production of PGE 2 and PGF 2a was enhanced by CRH in vitro (Jones and Challis, 1989). Since PGE 2 (Dibbs et al, 1997) and interleukin 1b (Petraglia et al, 1990) themselves increase the CRH synthesis of trophoblast cells, this may constitute a positive paracrine feedback loop resulting in labour and delivery. In addition, CRH stimulates the synthesis of oxytocin in the placenta (Florio et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Another possible site of action of prostaglandins on the CRH promoter is the cAMP response element (CRE), located at –224, and its binding protein CREB [25]. Indeed, transfection experiments showed that, in choriocarcinoma cell lines transfected with the CRH promoter linked to luciferase, PGE 2 stimulated the activity of the promoter via a cAMP-dependent pathway [41]. The ability of the CRE motif to mediate the effects of prostaglandins on gene expression is further supported by findings on other prostaglandin-regulated genes.…”
Section: Discussionmentioning
confidence: 99%
“…moreover, women in the midluteal phase, when both progesterone and estrogen levels are relatively high, show enhanced aCTH levels in response to a stressor [32]. estrogens acting centrally, including in the pituitary corticotrophs and hypothalamus, are able to modulate the stress responses [33], and direct estrogenic regulation of CRF gene expression has been demonstrated in various tissues [34,35]. estrogen would regulate the HPa axis by stimulation of CRF gene expression in the hypothalamus in vivo, since high levels of estrogen replacement increases basal levels of CRF mRNa in the PVN of ovariectomized rats [30].…”
Section: Involvement Of Estrogen On Crf Gene Transcriptionmentioning
confidence: 99%